PRAGMATIC ANALYSIS OF RAFEEF ZIADAH'S "WE TEACH LIFE, SIR" - Syah Putra, Aidil; Meirandani, Amanda; Putri S, Erningsih (VARIABLE RESEARCH JOURNAL, 2024)
This study examines the pragmatic elements in Rafeef Ziadah's poem "We Teach Life, Sir," focusing on how linguistic context, deixis, presupposition, and speech acts contribute to its multifaceted layers of meaning. Employing a qualitative content analysis approach, the research delves into the poem's use of deictic expressions to anchor the reader in specific contexts, the presuppositions that create a shared understanding between poet and audience, and the speech acts that engage and elicit responses. The findings reveal how these pragmatic elements enhance the poem's emotional and political impact, offering a deeper understanding of the Palestinian experience as articulated through Ziadah's powerful language. This study contributes to the broader field of pragmatic analysis in poetry, demonstrating the value of examining linguistic and contextual nuances in literary texts.